Financial Constraints, Asset Tangibility, and Corporate Investment - Almeida, Heitor; Campello, Murillo (Review of Financial Studies, 2007)
[Pledgeable assets support more borrowing, which allows for further investment in pledgeable assets. We use this credit multiplier to identify the impact of financing frictions on corporate investment. The multiplier suggests that investment-cash flow sensitivities should be increasing in the tangibility of firms' assets (a proxy for pledgeability), but only if firms are financially constrained. Our empirical results confirm this theoretical prediction. Our approach is not subject to the Kaplan and Zingales (1997) critique, and sidesteps problems stemming from unobservable variation in investment opportunities. Thus, our results strongly suggest that financing frictions affect investment decisions.]